Islamic accountants and the quest for professionalization in Indonesia: Opportunities, challenges, and institutional legitimacy - Maulana, Aviandi Okta (Jurnal Akuntansi dan Auditing Indonesia, 2026)
This study investigates the professionalization of Islamic accountants in Indonesia, an under-researched area in the Islamic accounting and accounting profession literature. Although Islamic finance has increased the demand for Sharia-compliant reporting and specialized accounting expertise, the professional status of Islamic accountants remains unclear. Drawing on the professional systems framework developed by Abbott (2014), this qualitative study examines professional work through its objective and subjective dimensions based on semi-structured interviews with 11 key stakeholders, including regulators, practitioners, and academics. The findings show that the professionalization of Islamic accountants is shaped by the interdependence between subjective and objective dimensions. Subjective factors include the evolving professional identity of Islamic accountants, societal perceptions and acceptance, and the debate over integration versus independence. Objective factors include standardization and certification, education and competency, and regulation and governance. This study contributes to the Islamic accounting literature by positioning Islamic accountants as emerging professional actors in Indonesia’s Islamic financial industry.